2011
DOI: 10.1029/2010jf001797
|View full text |Cite
|
Sign up to set email alerts
|

Process-based modeling of tsunami inundation and sediment transport

Abstract: [1] The infrequent and unpredictable nature of tsunamis precludes the use of field experiments to measure the hydrodynamic and sediment transport processes that occur. Instead, these processes are often approximated from laboratory, numerical, and theoretical studies or inferred from observations of the resultant sediment deposits. Here Delft3D, a three-dimensional numerical model, is used to simulate the inundation and sediment transport of a tsunami similar in magnitude to the 26 December 2004 Indian Ocean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 76 publications
5
61
0
Order By: Relevance
“…Our simulation shows that the modified settling velocity does not cause noticeable changes in the deposit thickness or the scour depth; our results are consistent with those of Apotsos et al (2011), who considered the combined effects of hindered settling and stratification. However, for 3D models, Apotsos et al (2011) found the significant influence of hindered settling velocity on the deposit thickness if the mixing of sediment into water was not reduced by the density stratification due to the high concentration of suspended sediment. 4.3 Hydrodynamics and sediment transport for scenario S3 We examine scenario S3 in Table 4, which has a negative leading wave.…”
Section: Characteristics Of Tsunami Depositssupporting
confidence: 81%
See 2 more Smart Citations
“…Our simulation shows that the modified settling velocity does not cause noticeable changes in the deposit thickness or the scour depth; our results are consistent with those of Apotsos et al (2011), who considered the combined effects of hindered settling and stratification. However, for 3D models, Apotsos et al (2011) found the significant influence of hindered settling velocity on the deposit thickness if the mixing of sediment into water was not reduced by the density stratification due to the high concentration of suspended sediment. 4.3 Hydrodynamics and sediment transport for scenario S3 We examine scenario S3 in Table 4, which has a negative leading wave.…”
Section: Characteristics Of Tsunami Depositssupporting
confidence: 81%
“…This phenomena is consistent with the bathymetric surveys conducted at Kuala Meurisi (a site about 100 km south of Banda Aceh) following the 2004 tsunami in which a large offshore bar was observed (Gelfenbaum et al, 2007). Apotsos et al (2011) attributed the formation of large offshore bars to collisions of the backwash flows and the up-rushing waves. A thin layer (about 5-30 cm thick) of sediment could be deposited in the city area, and a maximum scour depth of nearly 5 m might occur on the seaward side of the road, which is caused by the abrupt change of the erodible and non-erodible beach materials.…”
Section: Sediment Transport For Scenario S2 421 Erosion and Depositionsupporting
confidence: 72%
See 1 more Smart Citation
“…wave heights, wave lengths). Though some investigations (Kobayashi and Lawrence, 2004;Apotsos et al, 2011) claimed that the leading depression wave would cause little erosion during retreating stage of first wave. Meanwhile, smaller runup and weaker backwash flow would cause less sediment movement.…”
Section: Characteristics Of Tsunami Depositsmentioning
confidence: 99%
“…The sequence of a tsunami hitting the coast comprises a series of processes: from the tsunami generation and propagation, to coastal-zone hydrodynamics (including surf and swash zone dynamics), coastal inundation and wave-structure interactions with the built environment. Regarding the modeling part -and focusing on coastal inundation -exemplary reference can be made to the work of Borrero et al (2006), who used the MOST model (Titov and González, 1997) for tsunami generation and inundation in western Sumatra; Gayer et al (2010), who used the MIKE21 Flow Model FM to simulate inundation based on roughness maps for Indonesia; Omira et al (2010), who applied a modified version of the COMCOT model (Liu et al, 1998) to selected cases in Casablanca, Morocco; Apotsos et al (2011), who used the Delft3D model to study inundation and sediment transport by the 2004 SE Asia tsunami in measured and idealized morphologies; and Løvholt et al (2012), who used models based on the Boussinesq equations for tsunami propagation and nonlinear shallow-water wave equations for coastal inundation to simulate the 2011 Tohoku tsunami. Extending to coastal planning, vulnerability assessment and tsunami hazard mitigation, one may refer to the work of Bernard (2005), González et al (2009), Post et al (2009, Kumar et al (2010), Sørensen et al (2012) and González-Riancho et al (2014).…”
Section: Introductionmentioning
confidence: 99%